Monitoring the process of formation of ZnO from ZnO2 using in situ combined XRD/XAS technique. (31st May 2021) - Daley, Thomas; Opuni, Kwasi B; Raj, Edwin; Dent, Andrew J; Cibin, Giannantonio; Hyde, Timothy I; Sankar, Gopinathan
Abstract: Use of in situ combined x-ray diffraction and x-ray absorption spectroscopy for the study of the thermal decomposition of zinc peroxide to zinc oxide is reported here. Comparison of data extracted from both x-ray diffraction (XRD) and x-ray absorption spectroscopy (XAS) with thermo gravimetric analysis (TGA) enabled us to follow the nature of the conversion of ZnO2 to ZnO. A temperature range between 230 °C and 350 °C appears to show that a very poorly crystalline ZnO is formed prior to the formation of an ordered ZnO material. Both the decrease in white line intensity in the Zn K-edge XANES and resulting lower coordination numbers estimated from analysis of the Zn K-edge data of ZnO heated at 500 °C, in comparison to bulk ZnO, suggest that the ZnO produced by this method has significant defects in the system.